Legal Protection To Pedestrians In Samarinda - Suwardi Sagama (Syariah: Jurnal Hukum dan Pemikiran, 2020)
AbstractPopulation growth in Samarinda in 2017 and 2018 had an impact on the increasing development and significant growth of vehicles. Vehicle growth was not supported by the availability of parking lots, so the sidewalks became parking lots for vehicles. This research intended to find the legal protection for pedestrians in public spaces in Samarinda and its obstacles and supporting factors. The research method used was an empirical and juridical legal study by applying the laws and regulations as the basis for legal argumentation, as well as conducting interviews with relevant agencies related to research. Pedestrians in public spaces in Samarinda were protected by legal norms in Article 25 paragraph (1) of Law Number 22 of 2009 concerning Traffic and Road Transportation. Every road used for public traffic must have sidewalks for pedestrians. Sidewalks in Samarinda had become a place for hawkers to sell and for riders or drivers to park their vehicles. The inhibiting factors were the limited availability of the budget, sidewalks for trading by hawkers, sidewalks for parking lots. Supporting factors were legal certainty, the realization of law order, and legal protection for students. Keywords: Sidewalks; Pedestrians AbstrakPertumbuhan penduduk di Kota Samarinda pada tahun 2017 dan 2018 berdampak pada meningkatnya pembangunan dan pertumbuhan kendaraan bermotor yang signifikan. Pertumbuhan kendaraan tidak didukung dengan ketersediaan lahan parkir, sehingga trotoar menjadi tempar parkir kendaraan bermotor. Bagaimana perlindungan hukum kepada pejalan kaki pada ruang publik di Kota Samarinda dan apa faktor penghambat dan pendukungnya. Metode penelitian yang digunakan yuridis empiris dengan menerapakan peraturan perundang-undangan sebagai landasan argumentasi hukum. Serta melakukan wawancara kepada instansi terkait yang berhubungan dengan penelitian. Pejalan kaki pada ruang publik di Kota Samarinda dilindungi oleh norma hukum dalam Pasal 25 ayat (1) Undang-undang Nomor 22 Tahun 2009 tentang LLAJ. Setiap jalan yang digunakan untuk lalu lintas umum wajib dilengkapi trotoar untuk Pejalan Kaki. Trotoar di Kota Samarinda menjadi tempat berjualan pedagang kaki lima dan parkir kendaraan bermotor. Faktor penghambat yaitu ketersediaan anggaran yang terbatas, trotoar digunakan berdagang oleh pedagang kaki lima, trotoar menjadi tempat parkir kendaraan bermotor. Faktor pendukung yaitu adanya kepastian hukum, terwujudnya ketertiban hukum dan perlindungan hukum kepada siswa/i. Kata Kunci:  Trotoar; Pejalan Kaki